The Akkadian verb and its Semitic background - Kouwenberg, Bert (Languages of the ancient Near East, 2010)
Objective, structure, and method -- Structure and organization in the Akkadian verbal paradigm -- The paradigm of the G-stem The impact of gemination I : the imperfective iparrVs -- The perfective and the imperative -- The -- perfect -- The stative -- The nominal forms of the verbal paradigm -- The secondary members of the verbal paradigm -- The derived verbal stems: general features -- The impact of gemination II : the D-stem -- The prefix n- -- The prefix š- -- The t-infix and its ramifications -- Verb forms with reduplicaion -- The weak verbs -- The verbs with gutturals -- The verbal paradigm of Proto-Semitic